Combinative approach to generalization of meanings - Karen S. Khachatryan (Изд-во НАН РА)
We gain new meanings through the acquisition of communities, the revelation from experience and the creation of new meanings by combining the existing ones. We refine meanings by abstract classes combined by be-, have-, do- categories of relationships [1, 3, 7]. In the paper we present a novel combinative algorithm constructing new meanings by generalization of the given sets of meanings.
Keywords: Mathematics; Computer software